How Do Internal Capital Markets Work? Evidence from the Great Recession. (18th October 2019) - Buchuk, David; Larrain, Borja; Prem, Mounu; Urzúa Infante, Francisco
Abstract: We study the inner workings of internal capital markets during the 2008–09 recession using a unique dataset of loans between business group firms in an emerging market. Intragroup loans increase quickly during the recession. Firms that are more central in the ownership network simultaneously increase lending and borrowing. Acting like simple intermediaries, central firms do not increase net lending. Our results imply that formal control rights are essential for intermediation in internal capital markets, particularly during distress. In line with previous results on winner-picking, receivers of intragroup loans are high-Q, financially constrained firms, which also perform significantly better than providers during the recession.